Differential impact of TIM-3 ligands on NK cell function - Xin Zhang; Lazar Vujanovic; Riyue Bao; Robert L Ferris; Tullia C Bruno; Aditi Kulkarni; Hridesh Banerjee; Housaiyin Li; Juncheng Wang; Lawrence P Kane; Pragati Upadhyay; Jennifer L Anderson; et al. (Journal for ImmunoTherapy of Cancer)
Background The transmembrane protein T-cell immunoglobulin and mucin-domain containing molecule 3 (TIM-3) is an immune checkpoint receptor that is expressed by a variety of leukocyte subsets, particularly in the tumor microenvironment. An effective TIM-3-targeting therapy should account for multiple biological factors, including the disease setting, the specific cell types involved and their varying sensitivities to the four putative TIM-3 ligands (galectin-9, phosphatidylserine, high mobility group protein B1 and carcinoembryonic antigen cell adhesion molecule 1), each of which engages a unique binding site on the receptor’s variable immunoglobulin domain. The primary objectives of this study were to assess the prevalence and function of TIM-3+ natural killer (NK) cells in patients with head and neck squamous cell carcinoma (HNSCC), determine whether the four TIM-3 ligands differentially affect TIM-3+ NK cell functions, identify the most immunosuppressive ligand, and evaluate whether targeting ligand-mediated TIM-3 signaling enhances NK cell effector functions.Methods Single-cell RNA sequencing and flow cytometry were used to study the prevalence, phenotypes and function of TIM-3+ NK cells in HNSCC patient tumors and blood. In vitro killing, proliferation and cytokine production assays were implemented to evaluate whether the four TIM-3 ligands differentially modulate TIM-3+ NK cell functions, and whether disruption of TIM-3/ligand interaction can enhance NK cell-mediated antitumor effector mechanisms. Finally, The Cancer Genome Atlas survival analysis and digital spatial profiling were employed to study the potential impact of etiology-associated differences on patients with HNSCC outcomes.Results We demonstrate that TIM-3 is highly prevalent on circulating and tumor-infiltrating NK cells. It co-expresses with CD44 and marks NK cells with heightened effector potential. Among the four putative TIM-3 ligands, galectin-9 most consistently suppresses NK cell-mediated cytotoxicity and proliferation through TIM-3 and CD44 signaling, respectively, but promotes IFN-γ release in a TIM-3-dependent manner. Among patients with HNSCC, an elevated intratumoral TIM-3+ NK cell gene signature associates with worse outcomes, specifically in those with human papillomavirus (HPV)+ disease, potentially attributable to higher galectin-9 levels in HPV+ versus HPV− patients.Conclusions Our findings underscore the complex functional impact of TIM-3 ligand signaling, which is consistent with recent clinical trials suggesting that targeting TIM-3 alone is suboptimal as an immunotherapeutic approach for treating malignancies.